Faktor yang Berhubungan dengan Perilaku Penggunaan Alat Pelindung Diri di PT X - Lintang Qusnul Budi Setiawati; Denny Ardyanto (Media Gizi Kesmas, 2023)
Background: Poor use of personal protective equipment (PPE) is a form of unsafe action that can cause accidents an occupational disease. A person's behavior is influenced various factors. Several factors that influence a person's behavior in using PPE include age, years of service and worker attitudes towards the use of PPE. Objectives: This study aims to analyze the relationship between age, years of service, and attitudes of workers towards the use of PPE with the behavior of using PPE workers at PT X. Methods: This research was an observational study with a cross-sectional design. The determination of the sample in this study used a total sampling technique from a total population of 28 workers in the production division of PT X who served in the field. The variables studied in this study include age, years of service, attitudes towards the use of PPE, and behavior in using PPE. Data were analyzed using cross-tabulation and spearman correlation. Results: The results of the analysis showed that there was no significant relationship between age (p=0,218), years of service (p=0,566), and attitudes (p=0,291) of workers with the behavior of using PPE. Conclusions: Age, years of service, and attitude are not related to the behavior of PT X's production workers in using PPE. Companies are advised to improve supervision and conduct an assessment toward the use of PPE on workers. For further research is recommended to examine other factors related to the behavior of using PPE.